Artificial MicroRNA-Based Specific Gene Silencing of Grain Hardness Genes in Polyploid Cereals Appeared to Be Not Stable Over Transgenic Plant Generations - Gasparis, Sebastian; Kała, Maciej; Przyborowski, Mateusz; Orczyk, Waclaw; Nadolska-Orczyk, Anna (Frontiers in Plant Science, 2017)
Gene silencing by RNA interference (RNAi) is a particularly important tool in the study of gene function in polyploid cereal species for which the collections of natural or induced mutants are very limited. Previously we have been testing small interfering RNA (siRNA)-based approach of gene silencing in wheat and triticale. In this research artificial microRNAs (amiRs) were studied in the same species and the same target genes to compare effectiveness of both gene silencing pathways. amiR cassettes were designed to silence Puroindoline a (Pina) and Puroindoline b (Pinb) hardness genes in wheat and their orthologues Secaloindoline a (Sina) and Secaloindoline b (Sinb) genes in triticale. Each of the two cassettes contained 21 nt microRNA (miR) precursor derived from conserved regions of Pina/Sina or Pinb/Sinb genes respectively. Transgenic plants were obtained with high efficiency in two cultivars of wheat and one cultivar of triticale after using the Pinb-derived amiR vector for silencing of Pinb or Sinb respectively. Lack of transgenic plants in wheat or very low transformation efficiency in triticale was observed using the Pina-derived amiR cassette, despite large numbers of embryos attempted. Silencing of Pinb in wheat and Sinb in triticale was highly efficient in the T1 generation. The transcript level of Pinb in wheat was reduced up to 92% and Sinb in triticale was reduced up to 98%. Moreover, intended silencing of Pinb/Sinb with Pinb-derived amiR cassette was highly correlated with simultaneous silencing of Pina/Sina in the same transgenic plants. High downregulation of Pinb/Pina genes in T1 plants of wheat and Sinb/Sina genes in T1 plants of triticale was associated with strong expression of Pinb-derived amiR. Silencing of the target genes correlated with increased grain hardness in both species. Total protein content in the grains of transgenic wheat was significantly lower. Although, the Pinb-derived amiR cassette was stably inherited in the T2 generation of wheat and triticale the silencing effect including strongly decreased expression of silenced genes as well as strong expression of Pinb-derived amiR was not transmitted. Advantages and disadvantages of posttranscriptional silencing of target genes by means of amiR and siRNA-based approaches in polyploid cereals are discussed.